Review of Institutional Safeguards. (Policy Papers; Policy Paper ;, 2022)
Ensuring the integrity of data and analysis is fundamental to the Fund's ability to deliver on its mandate. As part of the Fund's institutional safeguards review, a Working Group on Data and Analysis Integrity (WGDAI) was established to assess the possible need for changes in processes safeguarding the integrity of data and analysis at the Fund. The IMF primarily uses data supplied by its membership to fulfil its core mandate. The IMF has initiated and progressively enhanced a number of initiatives to help members prepare official data of adequate quality. Assessing data integrity and supporting countries' efforts to achieve high standards has required a sustained commitment on the part of the Fund.